2021
DOI: 10.2337/dc20-2791
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Autoantibody-Negative Type 1 Diabetes in Children, Adolescents, and Young Adults During the First Wave of the COVID-19 Pandemic in Germany

Abstract: The aim of this study was to investigate the frequency of newly diagnosed type 1 diabetes without evidence of autoimmunity and the respective frequencies of ketoacidosis in children, adolescents, and young adults during the coronavirus disease 2019 (COVID-19) pandemic in Germany compared with the previous decade. RESEARCH DESIGN AND METHODSBased on data from the German Diabetes Prospective Follow-up Registry (DPV), we compared data from 715 children, adolescents, and young adults, newly diagnosed with type 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 32 publications
(21 reference statements)
2
25
1
Order By: Relevance
“… 13 In another analysis of newly diagnosed T1D across Germany during the first wave of the pandemic (March 1 to June 30, 2020), there was no increase in T1D diagnosis in this time frame compared to the prior 8 years. 16 , 17 While these previous studies are limited by small sample sizes and include data from only the first wave of the pandemic, our analysis offers a first look at the longitudinal data spanning multiple institutions across the United States, multiple waves of the pandemic, and a diverse patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 In another analysis of newly diagnosed T1D across Germany during the first wave of the pandemic (March 1 to June 30, 2020), there was no increase in T1D diagnosis in this time frame compared to the prior 8 years. 16 , 17 While these previous studies are limited by small sample sizes and include data from only the first wave of the pandemic, our analysis offers a first look at the longitudinal data spanning multiple institutions across the United States, multiple waves of the pandemic, and a diverse patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, published reports have shown conflicting findings, with some reports suggesting an increase in newly diagnosed T1D in children and adolescents, 13 , 14 , 15 and others showing no change in expected or actual numbers of newly diagnosed T1D. 16 , 17 Our objective for this study was to describe trends in newly diagnosed T1D, as well as the severity of presentation at diagnosis during COVID‐19 compared to the prior year using data from seven large U.S. clinical centers.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, insulin deficiency due to direct destruction of beta cells by SARS-CoV-2 does not seem to play an important role in children with newly diagnosed type 1 diabetes. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a German study showed that COVID-19 infection did not increase type 1 diabetes cases when there was no evidence of autoimmunity. Importantly, this study only covered the first wave of the pandemic in Germany (approximately four months period) ( 54 ). Thus, possible links cannot be entirely ruled out, but larger studies are needed to confirm them.…”
Section: Discussionmentioning
confidence: 99%